Desperate and glorious John Mulvany's "Custer's last rally" - O'Sullivan, Niamh 1960- (2022)
The American Civil War (1861-1865) provided the immigrant Irish with an opportunity to display their loyalty and integrate. John Mulvany (c.1839-1906) played his part as a combatant illustrator and painter of the war. While the United States was celebrating its hundredth anniversary in 1876, news of the defeat at the Battle of the Little Bighorn in the Black Hills rocked the country. The battle was a defining event in the long claim by American settlers to conquer and colonize Native American land. Mulvany commemorated the catastrophe in the emblematic painting Custer’s Last Rally (1881). Patriotic, thrilling, and inspiring, the painting went on a nationwide tour and caused a sensation. Three Irishmen featured in the formation of the subsequent Custer myth: the journalists James J. O’Kelly and John F. Finerty, and, in its visual definition, the artist Mulvany. In the United States the Irish formed into militant nationalist organizations that campaigned against British colonial rule in Ireland. But intent on establishing themselves in the New World many lent their support to whitewashing the Black Hills. If the Irish turned on blacks to be recognized as white, they turned on Indians to be identified as American. Mulvany’s Western subjects were considered quintessentially American, but the picture that made his name was Custer’s Last Rally. Followed by his Irish counterpoint The Battle of Aughrim in 1885, these paintings celebrated the valour of the defeated. Just as Aughrim become a rallying call for the cause of Catholic Ireland, Custer’s last stand generated a heroic version of failure, for white Americans.
Keywords: Mulvaney, John -- 1844-1906; Nationalbewusstsein; Schlachtenbild; Irland; USA